2022
DOI: 10.1097/mao.0000000000003707
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Robotics-Assisted and Manual Insertions of Cochlear Implant Electrode Arrays

Abstract: HypothesisRobotics-assisted cochlear implant (CI) insertions will result in reduced intracochlear trauma when compared with manual, across multiple users.BackgroundWhether intracochlear trauma and translocations are two factors that may contribute to significant variability in CI outcomes remains to be seen. To address this issue, we have developed a robotics-assisted insertion system designed to aid the surgeon in inserting electrode arrays with consistent speeds and reduced variability. This study evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Importantly, they determined the robot-assisted procedures resulted in lower rates of translocation and were therefore less traumatic than the procedures that used manual insertion techniques. Previous cadaveric studies evaluating a similar robotic-assisted insertion device to that used in this clinical study have suggested an overall decrease in the cochlea trauma score with robotic-assisted insertions compared with manual in cadaveric insertions (30). The novelty of the current device can be highlighted by examining the differences in the robotic systems used by Daoudi et al versus the one reported in this clinical study.…”
Section: Robotic-assisted Insertion Of CI Electrodementioning
confidence: 70%
See 1 more Smart Citation
“…Importantly, they determined the robot-assisted procedures resulted in lower rates of translocation and were therefore less traumatic than the procedures that used manual insertion techniques. Previous cadaveric studies evaluating a similar robotic-assisted insertion device to that used in this clinical study have suggested an overall decrease in the cochlea trauma score with robotic-assisted insertions compared with manual in cadaveric insertions (30). The novelty of the current device can be highlighted by examining the differences in the robotic systems used by Daoudi et al versus the one reported in this clinical study.…”
Section: Robotic-assisted Insertion Of CI Electrodementioning
confidence: 70%
“…A recent systematic review evaluating tip fold-over with straight electrodes found an incidence of 0.1-1.3% depending on the study (31). Additionally, other clinical studies evaluating the effects of robotic-assisted insertion on safety have found that tip fold-overs are less likely to occur with robotic-assisted insertions because of the consistent insertion speed (30,32). The results of the current study extend the current body of knowledge on this subject, although more direct comparative studies are needed.…”
Section: Robotic-assisted Insertion Of CI Electrodementioning
confidence: 99%
“…Suggested alternatives, such as intraoperative imaging or optical tracking, have limited implementation in current clinical practice. Slower and more atraumatic array placements are reported to have been achieved with robot-assisted insertion devices, currently under development [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robotics-assisted EA insertion is an emerging technique in hearing preservation CI that can overcome the limitations of manual insertion, with studies suggesting lower rates of translocation and cochlear trauma (7,(21)(22)(23)(24). Our group has previously described the clinical safety and utility of a single-use robotic-assisted CI EA insertion device that can delicately insert an array at constant speed as low as 0.1 mm/s (11).…”
Section: Introductionmentioning
confidence: 99%